Kajian Literatur Efektivitas Electronic Word of Mouth (E-WoM) dalam Meningkatkan Minat Beli Konsumen di Sosial Media - Damayanti, Yosinta (Jurnal Manajemen dan Inovasi (MANOVA), 2019)
Today the development of technology is very fast, especially in the field of marketing. One of the proof is the emergence of Electronic Word of Mouth or e-WOM which is the next development of Word of Mouth or WOM. E-WOM is a support facility of businessmen in providing perceptions of good value for customers on social media. E-WOM used as communication in the marketing field on social media is offered to increase consumer buying interest in the products offered. E-WOM contains shared messages by consumers that related to purchases products, and can be used as a medium for delivering information related to products, both in terms of quality, or in terms of service provided by the seller. A lot of the companies have successfully understood the power of electronic word of mouth (e-WOM) on social media, this can be seen from the proliferation of companies offering their products on social media by using e-WOM to provide good advice from the sale of products. The purpose of this research is to provide scientific development and insight related to the effectiveness of Electronic Word of Mouth (e-WOM) in increasing the purchase interest of consumers. The type of research used is descriptive qualitative with the study literature method. Overall, the results of this literature review can conclude that Electronic Word of Mouth (e-WOM) can increase purchase interest of consumers on social media. The results are supported by several studies that show e-WOM can increase purchase interest of the consumer on social media.